Aspekt brytyjski w działalności Stanisława Mikołajczyka jako wicepremiera Tymczasowego Rządu Jedności Narodowej (28 czerwca 1945 – 8 lutego 1947) - Matera, Paulina (Acta Universitatis Lodziensis. Folia Historica, 2001)
This article higlights the role of the British policy in the activity o f Stanisław Mikołajczyk after the Second World War when he had already become the Vice Prime Minister of the Polish Government established on the conference in Yalta in February 1945. During the war Mikołajczyk was the Prime Minister of the Polish Government in Exile since July 15th 1943 till November 23rd 1944. In that period he was under hard pressure of the British politicians (Winston Churchill and Anthony Eden) who wanted him to agree to Soviet demands according to which Poland should accept „Curzon line” as her eastern border. It was the condition of the re-establishment of the Polish-Soviet relations having been broken in April 1943. The British politicians insisted on it. Mikołajczyk who could not obtain the consensus within his own government to fulfil that condition, resigned from his post on November 23rd 1944. He decided to come back to Poland and become a member of Polish government dominated by communists depended on the Soviet Union. Mikołajczyk became the vice prime minister. He believed that future parliamentary elections would be supervised by international committee from Great Britain and the United States. He counted on the support of the majority of Poles for his party PSL (Polish Peasant Party). But Great Britain found no possibilities to support Mikołajczyk. Also the United States did not care about the fulfilment of Yalta’s statement which stipulated free elections in Poland. Mikołajczyk sent a lot of reports describing the situation of his oppositional party which due to the persecutions could not act in a normal way. He had a contact with the British journalists who imparled those news abroad. British government only sent the notes with disapproval of postponing the data of elections. The official Polish-British relations were getting worse and worse. The members of the Communist Party (PPR) called Mikołajczyk „an imperialist agent” . They accused him of acting against Polish reasons of State. That is why his contacts with the British ambassador in Poland Victor Cavendish-Bentinck were strictly limited. Mikołajczyk was also supervised by Polish political police. Still he was disappointed by British opinion about Polish western border. During the Second World War the British politicians suggested him that Poland would obtain territorial compensation from Germany for the losses in the east. But once the war had been over they changed their attitude. British politicians wanted Mikołajczyk’s party to join the communist’s block of parties and resign the opposition before the elections. Formally they supported him but in fact they could not do anything to give him a real help so they lose their interest in the future of Poland. Despite this fact Mikolajczyk’s party decided to take part in the elections on January 19th 1947. The majority voted for PSL but results of elections were forged. PSL received only 28 places for 444 in the parliament. British government had sent the note indicating that it was impossible to accept these elections but then no other action was undertaken. In October 1947 Mikołajczyk got an information that he would be arrested. He had asked for help American and British embassies and he escaped from Poland to London on the board of British ship „Baltavia” on October 20th 1947.